Trends in agricultural diversification: regional perspectives - Barghouti, Shawki ed. (World Bank WashingtonUS, 1992)
Stresses that policy instruments and objectives to stimulate the process of diversification differ by country. Points out that a common problem is the limited flexibility of agricultural systems in adjusting to economic, political and technological change, therby constraining the ability of farmers to adjust to shifting opportunities to maximize their benefits and minimize risk and uncertaincy. The studies on South East Asia explore diversification performance at the farm, regional and sectoral levels and examine the future role of government in the diversification process.